Description of the Level of Community Knowledge About DAGUSIBU at the Melur Pekanbaru Community Health Center - Meiriza Djohari; Ayu Indah Lestari Afandi; Dea Adilla; Dinda Zulfi Rosadi; Diova Yuswidia Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The rational use of medicine is one of the important aspects in maintaining public health. However, there are still many people who do not understand how to obtain, use, store, and dispose of drugs properly. To overcome this, the government through the Food and Drug Monitoring Agency (BPOM) has launched an educational program known as the DAGUSIBU concept (Get, Use, Store, and Dispose of Medicines Correctly). The purpose of this study was to determine the level of public knowledge about DAGUSIBU at Melur Health Center Pekanbaru, Riau. The research design carried out in this study was observational which was descriptive analytic, with a cross sectional research design, data collection techniques were carried out concurrently. The subjects of this study were people who came for treatment and bought medicine at Puskesmas Melur Pekanbaru. Data collection in this study used a questionnaire on the level of knowledge of the community. Based on the research that has been done about the description of the level of public knowledge about DAGUSIBU, the results obtained that the four dimensions namely Daptkan, Use, Save and Dispose are in the category strongly agree with a percentage of 76% and the category agree with a percentage of 24%. It can be concluded that the community of Puskesmas Melur Pekanbaru generally has a good knowledge of how to get, use, store and dispose of drugs.